The benefits of coordinated rehabilitation in the treatment of stroke patients: A literature review - L. Shuranova; J. Vacková; M. Míková (Medičnì Perspektivi, 2023)
The article reveals the features of coordinated rehabilitation – a process that leads to rehabilitating of people with neurological damage that limits their functionality. The purpose of the article is a literature review within the framework of GAJU 066/2022/S, funded by the grant agency of the South Bohemian University of Czech Budejovice, Czech Republic, examining the effectiveness of coordinated rehabilitation in patients recovering from strokes and the use of the standardized Functional Independence Measure (FIM) test to assess the patient’s condition. Data come from current Czech and foreign publications. The EDS multi-finder was used to search for literary sources. Document searches were from 2016-2022 in Czech and English. Search terms include post-stroke rehabilitation, FIM, rehabilitation after stroke, neurorehabilitation, and community based rehabilitation. The start of coordinated rehabilitation of stroke patients should be timely, long-term, comprehensive, and effective, involving a multidisciplinary approach and teamwork. It is essential to develop an individual approach and create a suitable individual plan that allows the use of the FIM test. This is the only way to establish long-term and mutually beneficial cooperation. As the cost of rehabilitation increases, the financial burden on the healthcare system also increases. Caring for a stroke patient also puts various burdens on the family. Successful rehabilitation can reduce the use of costly medicines and materials and decrease the need for nursing care and the term of hospital stay. The social costs of strokes are associated with long-term dependence and a low degree of resocialization. Considering the frequency of strokes and the associated disability, there is an increasing need for coordinated services within coordinated rehabilitation. Gaps in data on coordinated stroke rehabilitation should be filled by providing necessary information about long-term participation in community-based programs.